The KBRI Riyadh Family: Reviving Gamelan Traditions to Enhance Our Shared Cultural Identity - Cherry Rinaldi; Subianto Karoso (Journal of Practice Learning and Educational Development, 2025)
The gamelan tradition is an integral element of Indonesian culture, deeply rooted in philosophical and spiritual values that reflect the harmony, unity, and cooperation among individuals in society. For the Indonesian diaspora, particularly at the Indonesian Embassy in Riyadh (KBRI Riyadh), gamelan performances have been revived as a means to preserve cultural heritage and strengthen the sense of community and cultural identity among Indonesians living abroad. This activity serves not only to introduce traditional Indonesian music to younger generations but also offers an emotional connection to their ancestral culture, which may fade due to the distance from their homeland. This study aims to identify and understand the role of gamelan activities at KBRI Riyadh in reinforcing cultural identity within the Indonesian diaspora community, especially among the younger generation. The research employs a qualitative analysis using NVivo software, which facilitates the mapping and categorization of interview data from participants. Through this approach, the study reveals the experiences, challenges, and benefits encountered by participants in gamelan activities. Some questions asked include the personal and cultural significance of gamelan to the participants, their initial experience in playing gamelan, and the impact of this activity on their understanding and appreciation of Indonesian culture. The findings indicate that gamelan plays a significant role in shaping cultural identity and fostering social bonds within the diaspora community. Participants acknowledge that by engaging in this activity, they feel more connected to their Indonesian roots and take pride in passing on this tradition to the next generation. Furthermore, gamelan activities at KBRI Riyadh have created a strong sense of solidarity among participants, helping them build closer social ties and a shared sense of togetherness. Overall, this study highlights the importance of gamelan activities as a medium to reinforce cultural identity within the Indonesian diaspora. By deepening their appreciation of gamelan, participants not only gain a more profound understanding of Indonesian culture but also strengthen the connections among members of the diaspora community. This study recommends that KBRI Riyadh continue to support and expand gamelan activities, allowing more community members to engage and experience its benefits in fostering a shared cultural identity.